The Performance of the Socially Responsible Investment Index in Indonesia - Bintang Ramadhan Putra; Reza Faisal Husein (Journal of Finance and Islamic Banking, 2021)
In Indonesia, several stock indices can be used as a reference in investing in stocks, such as the LQ-45, JII, and SRI-KEHATI stock indexes. The SRI-KEHATI stock index emphasizes its attention to sustainable and responsible investment (SRI), which is a manifestation of socially responsible investing, a perspective in investing where attention to ethics, social, and normative views of investors influences investors' decisions in investing. The purpose of the study was to compare the performance of SRI-KEHATI stock indexes against LQ-45 and JII based on risk-adjusted return using Sharpe, Treynor, and Jensen's Alpha ratios with an observation period from January 2015 to December 2019. The results showed that the overall performance of the SRI-KEHATI stock index managed to outperform the performances of LQ-45 and JII. Based on these results, investors can look at the stocks listed in the SRI-KEHATI stock index because, in addition to getting.